2022
DOI: 10.3390/biomedicines10092121
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-29s in Human Cancers—An Update

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that directly bind to the 3’ untranslated region (3’-UTR) of the target mRNAs to inhibit their expression. The miRNA-29s (miR-29s) are suggested to be either tumor suppressors or oncogenic miRNAs that are strongly dysregulated in various types of cancer. Their dysregulation alters the expression of their target genes, thereby exerting influence on different cellular pathways including cell proliferation, apoptosis, migration, and invasion, thereby contributing to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“… 124 Additionally, miR-29c is significantly downregulated in pancreatic cancer, which correlates with hyperactive Wingless-related integration site (Wnt) signaling pathways. 125 …”
Section: Effect Of Mirnas In Cancer and Cancer Therapymentioning
confidence: 99%
“… 124 Additionally, miR-29c is significantly downregulated in pancreatic cancer, which correlates with hyperactive Wingless-related integration site (Wnt) signaling pathways. 125 …”
Section: Effect Of Mirnas In Cancer and Cancer Therapymentioning
confidence: 99%
“…The authors also demonstrated how pharmacologically inhibiting miR-22 improved the survival of mice with breast tumors, highlighting the possible use of miRNAs as targets for therapeutic development [18]. In their review, Nguyen et al [19] summarized how miR-29s can have opposite roles in different human cancers, acting as either oncogene or tumor suppressors. Chiantore et al [20] defined a miRNA signature in actinic keratosis, a skin condition that can lead to cancer, that may affect the pathways involved in tumor development.…”
Section: Mirnas In Human Diseasesmentioning
confidence: 99%
“…By understanding the miRNA regulations that involve in the pathogenesis of infectious diseases, miRNAs could be used as biomarkers to detect diseases. Recently, several studies have focused on miRNAs, which can be used as a diagnostic tool for the identification of diseases, cancer, thermal tolerance effect, and reproductive and other stress effects in mammals and aquatic organisms [88][89][90][91][92][93][94][95][96][97][98]. For example, the report of El-Sebaey et al (2020) described that Cfa-miR-122 and -21 could be used as serum biological markers to detect primary hepatitis in dogs as they were differentially expressed between the acute hepatitis group, chronic active hepatitis group, and healthy group [88].…”
Section: Micrornas Used As Biomarkersmentioning
confidence: 99%